Structural and ComputationalModel ofe-Governance in Smart cities (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Some of the states in India claimed they already created a smart city. Principally the claimbased mostly of IT utilization for their governance. This section focuses on the presentrelationships among governance and smart cities, specifically within the smart city literature.There is no clear definition regarding the smart city governance. In general, a smart citydefinition is to explain a developed geographic region that makes property economicdevelopment and prime quality of life by excelling in - (1) government of a smart city, (2)smart decision-making, (3) smart administration and (4) smarttown collaboration. In turn, Iaddress the governance in smart cities as a replacement sort of collaboration through theemployment of ICTs. In this paper I will discuss two important terms Great GovernanceIndex (GGI) and Data Governance. The aim is to map e-government condition by measureindicators of smart government, that are: clear governance and open information for thegeneral public. Thus, new and innovative sorts of governance area unit required to deal withthe challenges of smart cities going on the far side the standard establishments and thereforethe classical processes of governing (Bolívar, 2016). This analysis is outbound from publicinfo revealing law and to correspond with the existence law. By examining governmenttransparency, the output of the analysis will be accustomed live the effectiveness of publicinfo revealing law and to see the condition of e-government in authorities within which as apart of a smart city.